Poisoning effect of N-containing compounds on performance of Raney® nickel in transfer hydrogenation - Alexey A. Philippov (Elsevier, 2021)
The effect of amines, imines and heterocycle compounds on conversion has been studied in transfer hydrogenation of camphor and 2-PrOH catalyzed by Raney® nickel. Small amount (5 mol% to nickel) of N-containing compound significantly decreases catalyst activity. It has been shown that the poisoning effect mostly depends on molecular size of amines and heterocyclic compounds. For aniline and cyclohexylamine the dependence of camphor conversion on poison/nickel ratio was obtained. Additionally, benzaldehyde, cinnamaldehyde demonstrated higher reactivity compared corresponding imines under transfer hydrogenation conditions. Obtained data explain low activity of nickel-based catalysts when N-containing compounds are presented in reaction mixture.